D2.2 Advances in molecular diagnostics in paediatric haematology oncology. (4th October 2017) - Rao, A; Chalker, J; Wilkhu, L
Abstract : The genomic revolution has heralded the beginning of precision medicine, a novel approach to the treatment of children with malignant and non malignant haematology and oncology diseases. 'Precision' applies to tailoring the treatment of a child with cancer, minimising complications of therapy whilst achieving the best outcomes. At GOSH the haematology laboratory department has persevered towards this goal. In 2008 the Molecular Genetics Unit of the Haematology Diagnostic Laboratory (HCMDS) was established. The service was set up to provide a national service for patients with Severe Congenital Neutropenia (SCN). Originally all testing was developed using Sanger sequencing. In 2012 it became apparent that this growth in demand would outstrip our resources rapidly. We optimised a Next Generation Sequencing Panel (NGS) targeted to 54 genes for Myeloid disease. This platform has been hugely successful providing predictive and prognostic biomarkers of cancer. In 2015, successful grant applications to Olivia Hodson Fund and to BRC Research and Diagnostics Theme led to a custom designed NGS panel to test patients with bone marrow failure with a predisposition to develop leukaemia. The service has expanded, last year we tested 168 cases for up to 10 genes associated with SCN. In addition to SCN we had developed genetic testing for patients with MDS/MPN. We now analyse ~1800 genes per year for rare diseases (Figure 1 ). Analysing sequencing data has become ever more challenging as it is crucial to elucidate which variants are pathogenic and those of unknown significance. Establishment of a multi-disciplinary team of Clinical Genetics and Regional Genetics Service has helped enhance the cross fertilisation of molecular genetic knowledge between the two departments which is particularly relevant for those genetic mutations which have the potential for germline inheritance and hence the need to offer genetic counselling. In 2017, we have begun work to develop a diagnostic gene panel of over 100 genes for children with myeloid malignancy.